Pemanfaatan Sistem Informasi Geografis Untuk Memetakan Distribusi Stunting Menggunakan Metode Autokorelasi Morans’I - Sari, Rizky Yuspita; Nurhayati, Siti; Raharjo, Untoro Dwi; Sary, A’idah Haniyah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Stunting is a significant issue in Indonesia caused by nutritional deficiencies that can lead to slower growth, cognitive impairment, and learning disorders. The stunting rate in Indonesia in 2022 was 21.6%, and the government aims to reduce this rate to 14% by 2024. Meanwhile, the stunting rate in Kulon Progo Regency reached 14.8%, placing it as the second highest stunting rate in the Special Region of Yogyakarta Province. Therefore, an effective strategy is needed to implement the acceleration program for reducing stunting in Indonesia, particularly in Kulon Progo Regency. One approach to reducing stunting is utilizing geographic information systems to map the distribution of stunting cases and potential causes. This study aims to analyze the spatial distribution of stunting cases in Kulon Progo Regency. The research method is a descriptive quantitative study using a geographic information system application, ArcGIS. The subject of study covers all stunting cases in Kulon Progo Regency from 2021 to 2023 based on secondary data from the Kulon Progo Health Office with a total of 5986 cases. The results of the study showed that stunting cases in Kulon Progo district formed a random pattern with a Moran's index value of -0.063811, and a p-value of 0.869570. In addition, the number of integrated health posts in this area is quite evenly distributed with more than 50 integrated health posts.